Might School Performance Grow on Trees? Examining the Link Between “Greenness” and Academic Achievement in Urban, High-Poverty Schools - Kuo, Ming; Browning, Matthew H. E. M.; Sachdeva, Sonya; Lee, Kangjae; Westphal, Lynne (Frontiers in Psychology, 2018)
In the United States, schools serving urban, low-income students are among the lowest-performing academically. Previous research in relatively well-off populations has linked vegetation in schoolyards and surrounding neighborhoods to better school performance even after controlling for important confounding factors, raising the tantalizing possibility that greening might boost academic achievement. This study extended previous cross-sectional research on the “greenness”-academic achievement link to a public school district in which nine out of ten children were eligible for free lunch. In generalized linear mixed models, Light Detection and Ranging-based measurements of green cover for 318 Chicago public schools predicted statistically significantly better school performance on standardized tests of math, with marginally statistically significant results for reading ––even after controlling for disadvantage, an index combining poverty and minority status. Pupil/teacher ratio could not account for the greenness-performance link. Interactions between greenness and disadvantage suggest that in schools with extreme levels of disadvantage (99% free lunch eligible, 100% minority status) the greenness-academic achievement link was not as strong, although still positive. To determine what forms of green cover were most strongly tied to academic achievement, tree cover was examined separately from grass and shrub cover; only tree cover predicted school performance. Further analyses examined the unique contributions of “school tree cover” (tree cover for the schoolyard and a 25m buffer) and “neighborhood tree cover” (tree cover for the remainder of a school’s attendance catchment area). School greenness predicted math achievement when neighborhood greenness was controlled for, but neighborhood greenness did not significantly predict either reading or math achievement when school greenness was taken into account. Future research needs to assess whether greening schoolyards boost school performance.